X-ray computerised tomography for fracture and facies characterisation and slab orientation in cores stored within aluminium tubes. Issue 1 (1st December 2019) - Esteban, Lionel; Barranco, Ishtar; Sarout, Joel
Summary: A 3D image of a whole core section can be generated by stacking contiguous cross-sectional slices from Medical X-ray Computerised Tomography (Medical XCT). This methodology was applied in cores sealed within aluminium barrels allowing selective and orientated slabbing. It was also used in wax-preserved cores. The resolution of the 3D images ( 120 μm) was similar to core photos allowing direct sedimentological and fracture description of the preserved core sections while maintaining the preservation. The 3D image reconstruction of the Medical XCT helped to identify internal features such as faults, macro-pores and fluids. With proper software analysis and appropriate calibration, it was also possible to measure angles of those particular geological and/or induced features with respect to a reference. This non-destructive technique was used on 210 metres of core, composed of sandstones with different intensities of carbonate cement, to measure the orientation of geological fractures and sedimentological structures. It provided the best slabbing angle for sections that were selected for further core characterisation. This technology can also be used to derive properties such as mineralogy, total porosity, connected porosity, pore shape and their orientation.